Inactivation of the superoxide dismutase by malondialdehyde in the nonalcoholic fatty liver disease: a combined molecular docking approach to clinical studies. (2nd November 2021) - Arya, Arash; Azarmehr, Nahid; Mansourian, Mahboubeh; Doustimotlagh, Amir Hossein
Abstract: The objective of the present study was to investigate the plasma levels of oxidative stress markers and the activity of antioxidant enzymes in NAFLD and healthy subjects. Furthermore, the interaction behaviors of malondialdehyde (MDA) with Cu/Zn superoxide dismutase (SOD1) enzyme were elucidated by molecular docking. The study involved 60 patients with NAFLD and 25 healthy volunteers. The plasma levels of oxidative stress parameters and antioxidant enzymes activity were determined. NAFLD patients had significantly higher alanine aminotransferase, MDA and nitric oxide metabolites values, as well as significantly lower total thiol and SOD activity than the control group. Based on the molecular docking, MDA could deactivate the enzymatic activity of SOD1. Impaired antioxidant defense systems may be involved in the progression of NAFLD. This study provides direct evidence at a molecular level to explain that MDA may exert its oxidant activity by specific action within the specific molecular pathway. Highlights: Impairing antioxidant defense systems may be a main factor in the progression of nonalcoholic fatty liver disease (NAFLD). Increasing MDA and NO metabolites, as well as decreasing TSH values and SOD activity in NAFLD patients as compared to control subjects Increasing MDA level in NAFLD patients may be inactivate SOD activity by reaction with the key residues Cu ion inside active site of the enzyme catalytic site.